Timor-Leste Country Program Evaluation, 2000-2010 : Evaluation of the World Bank Group Program - Independent Evaluation Group (Washington, DC: World Bank Group, 2015)
This country program evaluation (CPE) assesses the outcomes of the World Bank Group (WBG) program in Timor-Leste during the review period (2000 to 2010). The WBG’s strategy during this period was to support the government of the nascent country in three broad areas: (a) poverty alleviation and the provision of basic social services, including health and education; (b) development of state institutions, including creating good governance and building the capacity of state institutions; and (c) promoting sustainable nonpetroleum growth, especially through the development of agriculture and the private sector. The CPE rates the overall outcome of its support to the country over the review period as moderately unsatisfactory. The Bank Group strategy was broadly congruent with the country‘s own aspirations, but its relevance and effectiveness waned through the evaluation period. To boost the WBG‘s role as an effective partner in Timor Leste’s development, independent evaluation group (IEG) recommends that the WBG: (i) set its key objective as one of supporting vigorous and sustainable non-oil growth, creating jobs and improving infrastructure; (ii) in consultation with development partners, sharply prioritize its program, being realistic about time frames; (iii) increase its focus on effective human resource development for institution building and improved governance; (iv) follow more closely its own guidance on dealing with fragile states; (v) ensure more active management of its assistance program, strengthening its capacity to deliver timely high-quality policy and technical advice; (vi) be realistic with regard to the situation on the ground and what is needed to attain development objectives; (vii) make International Finance Corporation’s (IFC’s) interventions of sufficient scale to address the objectives of its program; and (viii) bolster monitoring and evaluation (M and E) by focusing on a few key results and improving statistical capacity to obtain reliable data of sufficient frequency.